Avaliação proteômica de plasma seminal de touros holandeses (Bos taurus) de alta e baixa fertilidades - Viana, Arabela Guedes de Azevedo (2018)
Among the factors determining mammalian spermatozoa physiology and fertilization capacity, there are proteins, which are found suspended in seminal plasma. Several studies have been carried out to describe and evaluate the proteome of seminal plasma of several species with different fertility conditions. This study aimed to analyze the seminal plasma proteome of Holstein bulls (Bos taurus). A comparative analysis between seminal plasma proteomes of bulls with high and low fertility was also carried out. Using a high-performance liquid chromatography coupled to mass spectrometry (HPLC-MS), the seminal plasma of ten bulls (divided equally between high and low fertility groups) from artificial insemination was described. In the total, 1.159 proteins were identified, of which 79 showed different abundance between the groups. Among the proteins, eight indicated a significant contribution to the definition of the fertility phenotype (P <0.05). Overexpressed proteins in high fertility bulls were the type C natriuretic peptide, metalloproteinase 2 inhibitor, sperm binding protein - 30kDa and sulfhydryl oxidase. Meanwhile, clusterin, tissue factor pathway 2 inhibitor, galectin-3 binding protein and 5'-nucleotidase were overexpressed in low fertility bulls. Then, a fertility classification index based on proteins abundance was calculated (Spearman's rho = 0.91). The results represent a major contribution to the construction for building a library of the bovine seminal proteins. In the future, through researches based in the data from present study and literature, biomarkers will be able to be used to improve reproductive biotechniques for bulls and other mammals, including humans.